STEAM-based Batik Activities as an Effort to Stimulate Cognitive Abilities - Hidayati, Novi; Widadiyah , Qorina (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The low cognitive abilities of early childhood and the lack of variety of media and methods used in learning mean that this research aims to look at STEAM-based batik activities in improving cognitive abilities in early childhood. This research approach is a mixed method with a focus on group B children aged 5-6 years in one of the kindergartens in Gebangudik District, Cirebon Regency. Data was collected using observation techniques and interviews. Interview data and observations of STEAM-based batik activities using a qualitative approach. Observational data on children's cognitive abilities will be analyzed using a quantitative approach. The results of this research show that STEAM-based batik activities can improve children's cognitive abilities with a percentage gain of 39% in the Starting to Develop category to 70% in the Developing According to Expectations category, especially in the ability to solve problems, think critically, develop reasoning power, and make decisions. Because this batik activity is modified into an activity that can make children explore their environment because this batik activity goes through several steps, namely patterning, wiping and batiking. Steps of activities that are integrated with the STEAM approach can improve the ability to solve problems, think critically, develop reasoning power, and make decisions.